Party's Line and Foreign Direct Investment in China: A Text Analysis - Tang, Zhaoji. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Economics.; Advisor: Enrico Spolaore.; Committee: Elizabeth Remick.; Keyword: Economics.